Mathematical Modeling of Geological CO₂ Storage: Analysis of the Incorporation of the Hysteresis Effect in Relative Permeability Equations and Capillary Pressure - Franklin, Lucas Alexandre; Pinto , Aleson; Marina Pinnoti, Laura; Paula, Ana (Latin American Journal of Energy Research, 2025)
Geological CO₂ storage is one of the main strategies for mitigating greenhouse gas emissions. This study analyzes the effect of hysteresis on capillary pressure (Pc) and relative permeability (kr) curves, which are fundamental for understanding the multiphase behavior of CO₂ in porous media. Based on the Brooks–Corey (1964) and Killough (1976) models, and recent literature data, it was observed that considering hysteresis significantly alters the Pc and kr curves, increasing capillary and residual trapping while reducing CO₂ mobility. The results indicate that hysteretic models provide more realistic and reliable predictions regarding the efficiency and stability of geological carbon storage, especially in gas injection cycles.
Keywords: carbon dioxide; carbon storage; capillary trapping; hysteresis; numerical modeling